The Etymology of Specific Epithets for Plants of Trans-Ganga Plain Region - Sharma, Damini; Chauhan, Sandeep Kumar; Ghildiyal, Shivani; Deogade, Meena; Nesari, Tanuja M. (Indian Forester, 2025)
No Abstract.